AI DRIVEN CUSTOMER SERVICE IN BANKING - Jose, Nisha Mary; Biji Jose (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The adoption of Artificial Intelligence (AI) in banking has revolutionised customer service by offering efficient and personalised experiences. This study aims to explore the awareness and usage, and most widely used AI-driven customer service platforms in the banking sector. The study is focussed among educated and employed individuals in the Kottayam district of Kerala. Factor analysis is used to identify the awareness and usage of the AI driven customer services. The study highlights the significant benefits of AI in banking, including minimum response times, 24/7 availability, personalised interactions, and enhanced convenience. The study also examines the most popular AI driven platforms among respondents. By understanding the perceptions of educated employed individuals, the study can give suggestions for developing more inclusive and efficient AI strategies in the banking sector, promoting a balanced approach between technology and human centric services.